The Effect Of Isometric Handgrip Exercise In Reducing Blood Pressure Of Hypertension Patients In Bajoe Village, Soropia Subdistrict, Konawe Regency - Wikal Sulistia Dwi Putra; Amiruddin Eso; Pranita Aritrina Syafri; Yenti Purnamasari (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2024)
ABSTRACT Background. Hypertension is a condition where systolic blood pressure is ≥140 mmHg and diastolic pressure is ≥90 mmHg at rest. Isometric handgrip exercise is one type of exercise that is effective in reducing blood pressure in patients with hypertension. The purpose of this study was to determine the effect of isometric handgrip exercise in reducing blood pressure in hypertensive patients in Bajoe Village, Soropia Subdistrict, Konawe Regency. Methods. This study used a pre-experiment research design with a one group pretest posttest design approach with the independent variable being isometric handgrip exercise and the dependent variable being blood pressure. The sample in the study was the community of Bajoe Village, Soropia Subdistrict, Konawe Regency who suffered from hypertension as many as 30 people who were taken using Purposive Sampling technique and data analysis using Paired sample t test. Data obtained from blood pressure measurements measured before and after doing isometric handgrip exercise for 5 minutes in 5 consecutive days. Results. The results obtained from 30 samples showed that isometric handgrip exercise intervention reduced mean systolic blood pressure by 7.35 mmHg (p = 0.000) and mean diastolic blood pressure by 2.53 mmHg (p = 0.000). Conclusion. There is an effect of isometric handgrip exercise in reducing blood pressure of hypertensive patients in Bajoe Village, Soropia Subdistrict, Konawe Regency.